Microorganisms in soils of bovine production systems in tropical lowlands and tropical highlands in the department of Antioquia, Colombia (2018)
ABSTRACT : Studies on the physical and chemical effects of extensive grazing on soils have been performed in Colombia, but the effects of dairy cattle rearing on the biological properties of soils are not well known.The objective of this study was to evaluate microorganisms in 48 soils from livestock farms in the highland and lowland tropics in the Northern and Magdalena Medio subregions of the Department of Antioquia (Colombia). Principal component analysis demonstrated differences in the edaphic compositions of the soils, with increased percentages of root colonization by arbuscular mycorrhizal fungi and the density of microorganisms in farms that have soils with moderate phosphorus and nitrogen contents, low potassium content, and a moderately acidic pH. Agglomerative cluster analysis showed two groups for the highland tropic soils and six groups for the lowland tropic soils based on their population densities and interactions with the studied parameters. These results represent a first attempt to describe the density of microorganisms and the effect of soil physicochemical parameters on colonization by arbuscular mycorrhizal fungi in areas with determinant agroecological conditions, microbial functional diversity, and the presence ofmycorrhizal fungi in livestock farm soils in Colombia.